2020
DOI: 10.28991/cej-2020-03091629
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Accident Analysis and Identification of Black Spot Locations on Highway

Abstract: Road safety is the main problem in developing countries. Every year, millions of people die in road traffic accidents, resulting in huge losses of humankind and the economy. This study focuses on the road traffic accident analysis and identification of black spots on the Lahore-Islamabad Highway M-2. Official data of road traffic accidents were collected from National Highway and Highway Police (NH & MP) Pakistan. The data was digitized on MS Excel and Origin Pro. The accident Point weightage (APW) method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…Since 'human error' is the main cause of road traffic collisions, there have been attempts to minimize unfavorable driver behaviour in vehicles. In one example, researchers used more than a dozen alarms to prevent drivers from becoming overly fatigued (e.g., falling asleep) (Iqbal et al, 2020). These same lessons can likely be applied to ensure the safe operation of partially and conditionally automated vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Since 'human error' is the main cause of road traffic collisions, there have been attempts to minimize unfavorable driver behaviour in vehicles. In one example, researchers used more than a dozen alarms to prevent drivers from becoming overly fatigued (e.g., falling asleep) (Iqbal et al, 2020). These same lessons can likely be applied to ensure the safe operation of partially and conditionally automated vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these questionnaires usually report desirable behaviors, and there is the risk of recall bias which limits their objectivity [7] . Other new methods of observation of bicyclists, as yet not used in the UAE context, include monitoring by moving aerial cameras, video-based observation, or black spot identification [6,41,42] . However, such approaches would have the same limitations as our current methods.…”
Section: Discussionmentioning
confidence: 96%
“…[7] Other new methods of observation of bicyclists, as yet not used in the UAE context, include monitoring by moving aerial cameras, video-based observation, or black spot identification. [6,41,42] However, such approaches would have the same limitations as our current methods. We do not have access to detailed traffic injury police data, accordingly, we were unable to assess the relationship between cycling-related injuries and unsafe cycling behaviors.…”
Section: Limitations Of the Studymentioning
confidence: 97%
“…The most relevant factors related with driver injury severity were identified using a Multinomial Logit model [16]. Human error was highlighted as a major contributory element in road traffic accidents by Asad Iqbal et al (2020), and the Salt Range was classified as a black spot-on account of vehicle braking failure [17]. Minglei Song et al suggested a road accident prediction model based on joint probability density feature extraction from big data in 2019 [18].…”
Section: Literature Reviewmentioning
confidence: 99%